2021
DOI: 10.1186/s12974-021-02127-w
|View full text |Cite
|
Sign up to set email alerts
|

Specific depletion of resident microglia in the early stage of stroke reduces cerebral ischemic damage

Abstract: Background Ischemia can induce rapid activation of microglia in the brain. As key immunocompetent cells, reactive microglia play an important role in pathological development of ischemic stroke. However, the role of activated microglia during the development of ischemia remains controversial. Thus, we aimed to investigate the function of reactive microglia in the early stage of ischemic stroke. Methods A Rose Bengal photothrombosis model was applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 84 publications
2
50
0
Order By: Relevance
“…Microglial cells can damage neurons, oligodendrocytes, astrocytes and blood vessels in the early phase, releasing, e.g., ROS. However, in later stages, they may play a protective or repair role (M2 population) due to the release of TGF-beta1 (transforming growth factor beta 1), GDNF (glial cell derived neurotrophic factor) and the anti-inflammatory IL-10 (interleukin 10) (58)(59)(60).…”
Section: General Viewmentioning
confidence: 99%
“…Microglial cells can damage neurons, oligodendrocytes, astrocytes and blood vessels in the early phase, releasing, e.g., ROS. However, in later stages, they may play a protective or repair role (M2 population) due to the release of TGF-beta1 (transforming growth factor beta 1), GDNF (glial cell derived neurotrophic factor) and the anti-inflammatory IL-10 (interleukin 10) (58)(59)(60).…”
Section: General Viewmentioning
confidence: 99%
“…Neuroinflammation is prevalent in these conditions and plays with similar mechanisms. In the early stage of both SAH and AIS, the activation of microglia by neutrophil is vital for following cascade of inflammation, with similar inflammatory mediators and pathways ( 120 ). Moreover, Tregs also play a major role in immunomodulatory function and neuroprotection after AIS ( 121 ).…”
Section: Practice Prospectsmentioning
confidence: 99%
“…Microglial cells are widely activated by damage-associated molecular patterns released from injured neuronal cells, and subsequently, mediate drastic neuroin ammation during the acute stage of IS 26 . Previous studies have reported that de ciency of microglial cells inhibits the microglial cellmediated neuroin ammation, ultimately leading to the alleviation of IS in mouse models 27 . Our data showed that hypothermia suppressed the activation of microglial cells and shifts the polarization of microglial cells from pro-in ammatory phenotype to anti-in ammatory phenotype.…”
Section: Discussionmentioning
confidence: 97%